(untitled) (Applied Biological Research, 2018)
Molecular markers have proved a valuable source for assessing plant genetic resources by improving our understanding on the distribution and extent of genetic variability present within and among the species. In this study, genetic diversity among and between 16 parents and 12 hybrids of Populus deltoides were analyzed by SSRs (simple sequence repeats). The 18 selected SSR primers yielded 51 polymorphic scorable bands with PIC value of 0.77. The effective multiplex ratio and marker index were 1.82 and 0.80, respectively. Genetic similarity among the collections varied from 0.39 to 0.88 when pooled data of parents and hybrids were analyzed through UPGMA. The analysis of combined data set with SSR, clustered hybrids on dendrogram based on their relationship with parents. Thus, high polymorphism obtained indicates that SSR markers have potential for identification and characterization of genetic variation within and among Populus species.